The Shannon Mighty River of Ireland : A Tourism Masterplan for the Shannon 2020 - 2030 : Reimagining the River Shannon and Shannon Erne Waterway.: A Tourism Masterplan for the Shannon 2020 - 2030 : Reimagining the River Shannon and Shannon Erne Waterway. The Masterplan / Volume 2/5, (2020) - SLR Consulting,
No abstract available